Geospatial Intelligence Analysis to Predict Acts of Security Disturbance by KSTP in Nduga Regency, Papua Mountainous Province - Sumampouw, Giovanni Leonardo; Nurisnaeny, Poppy Setiawati (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
The problem of security disturbance actions with the aim of separatism, which has been carried out by the Papuan Separatist Movement Organization (KSTP), has resulted in many casualties, both civilians and TNI and Polri security forces, and threatens security stability in Papua. Intelligence is central in thwarting and eliminating threats to state sovereignty through active and systematic observation of potential threats, facilitating early detection. This research aims to provide an overview of the importance of geospatial intelligence (GEOINT) analysis in predicting the actions of security disturbances by KSTP in Nduga Regency, Papua Mountainous Province. The research method employed is the GEOINT methodology, based on the Mellion model, which comprises planning, information collection, processing, analysis, and dissemination phases. The results of the research conducted, namely GEOINT, have an important role in supporting the implementation of intelligence operations in Nduga Regency, because it produces a visual picture of the movement of KSTP through the geocoding process of security disturbance action information for the period May 2022 to June 2023.